Reversing the vectors of meaning. The diagrammatic language of Vilém Flusser. - Irrgang, Daniel (Flusser Studies, 2020)
In the lecture manuscript which he purportedly wrote in 1980 - "Image and Text" (Flusser 1980) 12 - Flusser went straight to the heart of these strange semantics of the techno-image: "They seem to be effects of the things they mean, not their symbols." 11 But if Flusser had, even as late as 1989, difficulties to find examples for concrete techno-images, he, in an earlier phase of his writing, as the techno-image concept was still in a state of defining, actually gave quite useful examples for technical images. Yet, it's difficult - even in the later years, as Flusser's interest in the synthetic, computer-generated image increased - to speak of a theory of techno-images (as in a consistent theoretical model), not only because of the dynamic character of Flusser's concept formation. Drafts of techno-images: Flusser's diagrammatic sketches Not only does Flusser's concept of the techno-image lend itself to diagrammatic analysis.